EVALUASI PENGELOLAAN LIMBAH PADAT MELALUI ANALISIS SWOT (Studi Pengelolaan Limbah Padat Di Kabupaten Jember) - Pujiati, Rahayu Sri; Sari, Putri Kurnia (FKM - UNEJ, 2010)
This research specifically addressed the issue of the mechanism of solid waste management at Jember regency. This was a chase study type by kualitatve approach. An analysis on the results of solid waste input-process-output evaluation revealed factors influencing the process of solid waste management as part of a strategic issue to be addressed by the DPU Cipta Karya dan Tata Ruang. Analysis Strength, Weakness, Opportunity, and Threath (SWOT) activity, a draft for an effort was chosen, from those projected, to serve as a reference for the resolution of future as well as current issues. Research results revealed DPU Cipta Karya dan Tata Ruang operations to be improving, as shown by the increase in number of service provided. Solid waste produced by each and every ward is categorized into organic solid waste and anorganic solid waste. The waste management involves shorting-out, stockpiling, transporting, and dissolving processes. Discrepancies between the application of this solid waste management process and the set standard operating procedure is evident. Issues arising in the application of waste management processes are strength on composting at Kreyongan and Talangsari; weakness show with the less of waste collecting infrastructure and dump truck same the type of waste ; opportunity and threath show by the support of stakeholders on composting and increasing the volume of solid waste. It is recommended to the hospital management to care more with the process management of solid waste by increasing awearness and number of service provided. Keywords : solid waste, SWOT analysis